2005
DOI: 10.1093/hmg/ddi188
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathogenetic mechanisms for PHOX2B associated polyalanine expansions and frameshift mutations in congenital central hypoventilation syndrome

Abstract: Congenital central hypoventilation syndrome (CCHS) is a rare neurocristopathy characterized by absence of adequate autonomic control of respiration with decreased sensitivity to hypoxia and hypercapnia. Frameshift mutations and polyalanine triplet expansions in the coding region of PHOX2B have been identified in the vast majority of CCHS patients and a correlation between length of the expanded region and severity of CCHS has been reported. In this work, we have undertaken in vitro analyses aimed at identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 33 publications
8
114
0
1
Order By: Relevance
“…These observations are consistent with the results obtained with FOXL2 and point to a common pathogenic mechanism. A similar behavior has been observed for PHOX2B in cellular models (Bachetti et al, 2005;Trochet et al, 2005 A c c e p t e d M a n u s c r i p t 8 expansion in Arx transcription factor forms intranuclear inclusions and results in increased cell death suggesting a toxic effect (Nasrallah et al, 2004). Thus, it appears that this expansion lead to cellular toxicity as it was suggested for PABPN1.…”
Section: Mutations Affecting the Foxl2 Locussupporting
confidence: 73%
“…These observations are consistent with the results obtained with FOXL2 and point to a common pathogenic mechanism. A similar behavior has been observed for PHOX2B in cellular models (Bachetti et al, 2005;Trochet et al, 2005 A c c e p t e d M a n u s c r i p t 8 expansion in Arx transcription factor forms intranuclear inclusions and results in increased cell death suggesting a toxic effect (Nasrallah et al, 2004). Thus, it appears that this expansion lead to cellular toxicity as it was suggested for PABPN1.…”
Section: Mutations Affecting the Foxl2 Locussupporting
confidence: 73%
“…Alanine expansions may result in a protein that can bind to the correct targets in the genome but is unable to carry out its normal regulatory function and, therefore, competes with the product of the wild-type allele (4). In contrast, a single functional Phox2b allele may ensure correct protein function, leading to a less severe phenotype (8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that all alanine expansions tested lead to protein misfolding in vitro, resulting in cytoplasmic aggregation visible in HeLa cells only for proteins with more than a + 9 alanine expansion in our experiments (Bachetti et al, 2005;Trochet et al, 2005a). However, a gel filtration experiment indicated that PHOX2B expanded by only 5 alanines had a strong tendency to multimerize in vitro (Figure 2; Trochet et al, 2005a).…”
Section: Phox2b Expanded By 4 Alanines Does Not Multimerize In Vitromentioning
confidence: 45%